Essential Elements That Contribute to the Recovery of Persons With Severe Mental Illness: A Systematic Scoping Study - Jaiswal, Atul; Carmichael, Karin; Gupta, Shikha; Siemens, Tina; Crowley, Pavlina; Carlsson, Alexandra; Unsworth, Gord; Landry, Terry; Brown, Naomi (Frontiers in Psychiatry, 2020)
Introduction: There is an increasing emphasis on recovery-oriented care in the design and delivery of mental health services. Research has demonstrated that recovery-oriented services are understood differently depending on the stakeholders involved. Variations in interpretations of recovery lead to challenges in creating systematically organized environments that deliver a consistent recovery-oriented approach to care. The existing evidence on recovery-oriented practice is scattered and difficult to apply. Through this scoping study, we aim to identify and map the essential elements that contribute to recovery outcomes for persons living with severe mental illness. Methods: We used the Arksey & O'Malley framework as our guiding approach. Seven key databases (MEDLINE, PubMed, CINAHL/EBSCO, EMBASE, ProQuest, PsycINFO, and Google Scholar) were searched using index terms and keywords relating to recovery and severe mental illness. To be included, studies had to be peer-reviewed, published after 1988, had persons with severe mental illness as the focal population, and have used recovery in the context of mental health. The search was conducted in August 2018 and last updated in February 2020. Results: Out of 4496 sources identified, sixty (n = 60) sources were included that met all of the selection criteria. Three major elements of recovery that emerged from the synthesis (n = 60) include relationships, sense of meaning, and participation. Some sources (n = 23) highlighted specific elements such as hope, resilience, self-efficacy, spirituality, social support, empowerment, race/ethnicity etc. and their association with the processes underpinning recovery. Discussion: The findings of this study enable mental health professionals to incorporate the identified key elements into strategic interventions to facilitate recovery for clients with severe mental illness, and thereby facilitate recovery-oriented practice. The review also documents important gaps in knowledge related to the elements of recovery and identifies a critical need for future studies to address this issue.